The Importance Of Conversation In Helping Facilitate Communication In Academic Life - Nissa Zahra Silmy; Hafiz Azhar Nasution (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Often with the times, the use of English is often needed to build international relations. English is an international language used in almost all parts of the world. Therefore, understanding English conversation will help make communication easier and keep up with every development in the world. Conversation is a form of verbal communication between two or more people. In communication, the message is a very important part and is the goal to be conveyed. The form of conversation can be done formally or informally.